Product Market Regulation in Brazil - Vitale, Cristiana (OECD Publishing, 2022)
Appropriately designed and implemented regulations are powerful tools for enhancing economic performance. A strong and sound regulatory framework can mitigate threats to health, safety, and the environment and address market imperfections. However, regulation can also create barriers to the entry and expansion of firms, which may limit and distort competition. Some of these barriers are necessary, but others may go beyond what is needed to address the policy objectives and the market failure(s) regulation is intended to remedy. The OECD developed in the late 1990s a set of Product Market Regulation (PMR) Indicators to assess how competition-friendly the regulatory framework of a country is across a range of sectors and regulatory areas. A regulatory framework that facilitates competition, for example, can stimulate productivity by encouraging the efficient allocation of resources and promoting innovation and growth. This paper examines a range of product markets, services, and network industries in Brazil, relying on the results of the PMR indicators, and identifies areas where country's regulations could be brought more in line with international best practices. These include the governance of state-owned enterprises, interaction between policy makers and interest groups, network sectors, and professional services
Keywords: Economics; Brazil